Knowledge and Practice about Reproductive Health of Muslim Women in Patharaiya - Upadhayay, Parbati (Journal of Tikapur Multiple Campus, 2018)
The study entitled “Reproductive Health Status of Muslim Women in Kailali Districts” was to find out the general knowledge and practice about some components of reproductive health. the respondents of this study was Muslim married women who are in reproductive age group. There are 24 household of Muslim in Patharaiya VDC ward no. 1 and 4, total household were selected for data collection each women from each household was selected for respondents. Analysis of data reveals that 66 percent respondents got non formal education, few respondents (12.5%) got primary education but none got secondary on higher education. Most of the respondents (91.76%) had knowledge about family planning device but they did not practice it about 86 percent respondents did not use any kinds of device due to their religion. Percent respondents did not seek antenatal checkup form health institution, rather they prefer their relatives and neighbors. respondents felt shy for open talk about their pregnancy condition in the community. They have not knowledge about taking additional ion nutritional food during pregnancy period. Majority, 62 percent of the respondents delivered at home with the help of family members or neighbors in unhygienic conditions this caused various complications among the women of Muslim community. All most all (91%) respondents did not take postnatal care and they did not this may be the result of lack of knowledge, time and money also. The study shows that knowledge on reproductive health is very poor. Awareness should be created in the community to motivate women to utilize the health facilities this will in turn encourage them to seek antenatal and postnatal care. Moreover, focused should be on women who belong to the marginalized group.